2022
DOI: 10.1111/lam.13709
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional comparisons of the environmental microbiota of pond and tank environments at different locations for the commercial aquaculture of American shad

Abstract: The environmental microbiota plays a significant role in the growth and development of aquatic life. In recent years, American shad has become an important economic aquaculture species in China. However, information on the correlation between the growth of American shad and the aquaculture environment is limited. Through 16S rDNA‐based sequencing, the microbiota communities in ponds at different locations (Jiangyin and Yancheng in Jiangsu, China) were investigated. The results showed that the richness and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…No differences were found in the values of the F/B ratio, which is a well-documented factor whose changes have been used as a biomarker of intestinal dysbiosis in fishes ( 102 ). Our F/B values remain within the results reported for farmed fish, which vary widely depending on the rearing conditions and experimental diets utilized ( 103 , 104 ). On the other hand, the absence of differences in beta diversity (Weighted UniFrac) indicated that all samples were similar in terms of their phylogenetic features, and therefore, the addition of pungent spices to the diet did not pose a threat in terms of dysbiosis.…”
Section: Discussionsupporting
confidence: 86%
“…No differences were found in the values of the F/B ratio, which is a well-documented factor whose changes have been used as a biomarker of intestinal dysbiosis in fishes ( 102 ). Our F/B values remain within the results reported for farmed fish, which vary widely depending on the rearing conditions and experimental diets utilized ( 103 , 104 ). On the other hand, the absence of differences in beta diversity (Weighted UniFrac) indicated that all samples were similar in terms of their phylogenetic features, and therefore, the addition of pungent spices to the diet did not pose a threat in terms of dysbiosis.…”
Section: Discussionsupporting
confidence: 86%
“…Measurements of water temperature, pH, dissolved oxygen and conductivity were conducted in the eld utilizing the ProQuatro smart portable multiparameter water quality analyzer (YSI, Yellow Springs, OH, USA). In the light of a previously described method (Du et al 2022), the concentrations of ammonium nitrogen, nitrate nitrogen, nitrite nitrogen, total nitrogen and total phosphorus were determined. Phosphate levels were measured incompliance with the Chinese national environmental protection standard HJ 670-2013 "Water quality-Determination of orthophosphate and total phosphorus-Continuous ow analysis (CFA) and Ammonium molybdate spectrophotometry".…”
Section: Determination Of Aquatic Physicochemical Factorsmentioning
confidence: 99%
“…Phosphate levels were measured incompliance with the Chinese national environmental protection standard HJ 670-2013 "Water quality-Determination of orthophosphate and total phosphorus-Continuous ow analysis (CFA) and Ammonium molybdate spectrophotometry". The chemical oxygen demand was measured following the standard procedure outlined in ISO 8467:1993 (Du et al 2022).…”
Section: Determination Of Aquatic Physicochemical Factorsmentioning
confidence: 99%